2023
DOI: 10.1175/mwr-d-22-0087.1
|View full text |Cite
|
Sign up to set email alerts
|

Global Observing System Experiments within the Météo-France 4D-Var Data Assimilation System

Abstract: Observing System Experiments were undertaken within the 4D-Var data assimilation of the Météo-France global Numerical Weather Prediction (NWP) model. A six-month period was chosen (October 2019 - March 2020) where 40 millions of observations per day were assimilated. The importance of in-situ observations provided by aircraft, radiosondes and surface weather stations, despite their small fractional amount (7 %), has been confirmed particularly in the Northern Hemisphere. Moreover, the largest impact over Europ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…(1999) and has already been used with the ARPEGE model, as presented in Chambon et al . (2023). This norm is computed using the difference between the forecast of the experiments and the truth of the nature run, and by summing this forecast error for four different variables: surface pressure, temperature, wind speed, and relative humidity, with normalisation factors specific to each variable.…”
Section: Experimental Setup and Verification Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1999) and has already been used with the ARPEGE model, as presented in Chambon et al . (2023). This norm is computed using the difference between the forecast of the experiments and the truth of the nature run, and by summing this forecast error for four different variables: surface pressure, temperature, wind speed, and relative humidity, with normalisation factors specific to each variable.…”
Section: Experimental Setup and Verification Methodsmentioning
confidence: 99%
“…This norm is based on the same norm as the one used in the forecast sensitivity to observations index (FSOi), which is widely used among meteorological centres (Eyre, 2021), with adaptations to use the nature run as the reference instead of an analysis. It is computed using the energy norm proposed by Ehrendorfer et al (1999) and has already been used with the ARPEGE model, as presented in Chambon et al (2023). This norm is computed using the difference between the forecast of the experiments and the truth of the nature run, and by summing this forecast error for four different variables: surface pressure, temperature, wind speed, and relative humidity, with normalisation factors specific to each variable.…”
Section: Fsoi-like Metricmentioning
confidence: 99%
“…NWP centres often perform this type of experiment because of the need to test upgrades to operational systems and to conduct more systematic studies of the value of individual observing system components. Several studies have been conducted using OSEs, such as at ECMWF in the context of model upgrades (Kelly and Thépaut, 2007) and general observing system impact studies (Chambon et al ., 2022).…”
Section: Osse Designmentioning
confidence: 99%
“…An OSSE includes a "nature" run, or truth, generated by an NWP model; simulated observations produced using the appropriate forward operator; and data assimilation and forecast experiments to evaluate the impacts of the simulated observations using a different model. Numerous OSSE studies have shown the impacts of various observing strategies from terrestrial-based and space-based observing systems on weather prediction (Bormann et al, 2019;Bouttier & Kelly, 2001;Chambon et al, 2023;Cucurull et al, 2018;Errico et al, 2013Errico et al, , 2020Gelaro & Zhu, 2009;Jones et al, 2014;McCarty et al, 2021;Privé et al, 2021Privé et al, , 2022Singh et al, 2014;Wang et al, 2013). Harnisch et al (2013) used ensemble data assimilation techniques to evaluate the potential impacts of RO observation saturation and showed that RO saturation did not occur even with 128,000 soundings per day (corresponding to a global horizontal resolution of ∼63 km per day).…”
Section: Introductionmentioning
confidence: 99%